Pemanfaatan Aplikasi KAHOOT dalam Pembelajaran di Sekolah Dasar Negeri 2 - Lestari, Raniyah Ayu; Putra, Mardiansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The use of the KAHOOT application in learning at state elementary school 2 aims to introduce and train elementary school teachers in the use of the KAHOOT application. This activity is carried out as part of community service to improve the quality of learning in schools. In this socialization, elementary school teachers were given introductory and evaluation materials for the use of the KAHOOT application as an online-based measuring tool. The materials provided include an introduction to games, quizzes, discussions, and surveys that can be done through the KAHOOT application. In addition, teachers were also given training in creating online-based evaluation questions using the KAHOOT software. Discussions were also held with teachers to discuss the problems faced in using the KAHOOT application. In this socialization, lecture, practice, and question and answer methods were used to ensure a good understanding and application of the KAHOOT application in learning at state elementary school 2, aiming to improve the quality of learning and provide an interactive learning experience for students through the use of technology. , such as increasing student engagement, enriching learning experiences, and facilitating evaluation. However, it is important to ensure that the use of this application is in accordance with the context and needs of students and gets support and supervision from the school.